Development of BMAIN (Basic Motion Assisted Instruction) Learning Model for Recognition of Two-Dimensional Figure for Children with Mild Mental Retardation - Rubiana, Iman; Priana, Ari; Santika, Satya (Journal of Physical Education and Sports, 2018)
The purpose of this study is to develop a mathematical learning model that is combined with physical education learning for children with mild mental retardation in Extraordinary School. This game is called the PLAY (Basic Motion Assisted Instruction) game. This study uses the R & D (Research and Development) method that is carried out for mild mentally retarded students, Public Extraordinary School Tamansari, Tasikmalaya City, with the intention of developing a learning model for the introduction of the two-dimensional figure through physical activity. The results of the preliminary study or field findings are then described and analyzed so that these results are descriptive in the form of learning model models and learning steps concerning the purpose of the preliminary study and the results of expert trials and observations. The results of the preliminary study or field findings are then described and analyzed so that these results are descriptive in the form of learning model models and learning steps concerning the purpose of the preliminary study and the results of expert trials and observations.